2015
DOI: 10.1186/s40104-015-0018-z
|View full text |Cite
|
Sign up to set email alerts
|

The application of antimicrobial peptides as growth and health promoters for swine

Abstract: With the widespread ban on the use of antibiotics in swine feed, alternative measures need to be sought to maintain swine health and performance. Antimicrobial peptides (AMPs) are part of the nonspecific defense system and are natural antibiotics produced by plants, insects, mammalians, and micro-organisms as well as by chemical synthesis. Due to their broad microbicidal activity against various fungi, bacteria and enveloped viruses, AMPs are a potential alternative to conventional antibiotics for use in swine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
70
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(74 citation statements)
references
References 30 publications
1
70
1
2
Order By: Relevance
“…At present, the mechanisms of surfactin-promoting growth are not clear. From the results of previous researches, it could be concluded that the improved growth performances of different animals might be associated with the antimicrobial activity and function as potent immune regulators of AMPs (Hume 2011;Xiao et al 2015;Wang et al 2015). Further study is needed to reveal the detail mechanisms of surfactinpromoting growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, the mechanisms of surfactin-promoting growth are not clear. From the results of previous researches, it could be concluded that the improved growth performances of different animals might be associated with the antimicrobial activity and function as potent immune regulators of AMPs (Hume 2011;Xiao et al 2015;Wang et al 2015). Further study is needed to reveal the detail mechanisms of surfactinpromoting growth.…”
Section: Discussionmentioning
confidence: 99%
“…AMPs are produced by several species including bacteria, insects, amphibians and mammals as well as by chemical synthesis and genetically engineered micro-organisms (Wang et al 2015). In recent years, studies on AMPs and their applications have become one of the hot spots in the areas of agricultural science, biology, medicine, and physiology as well as having potential applications in medicine and the food industry (Xiao et al 2015). Supplementation with some AMPs has been reported to have positive effects on growth performance and immune function of fish (Peng et al 2007;Zhou et al 2008;He et al 2013;Shi et al 2014a).…”
Section: Introductionmentioning
confidence: 99%
“…It is able to reach the lower gastrointestinal tract and there excerts its effect. It has been shown that dietary supplementation with lactoferrin improves growth performance and reduces diarrhoea in pigs and decreases the counts of some potentially pathogenic gut bacteria as E. coli while increasing the numbers of potentially beneficial bacteria as lactobacilli and bifidobacteria (Yoon et al, 2012;Xiao et al, 2015a). Furthermore, it has been shown that the supplementation of pig diets with AMPs may increase villus height and crypt depth in the jejunum and ileum (Xiao et al, 2015a).…”
Section: Dietary Supplementation Of Insect Ampsmentioning
confidence: 99%
“…The use of AMPs may be a promising alternative to antibiotics Xiao et al, 2013aXiao et al, ,b, 2015aYoon et al, 2013Yoon et al, , 2014Yi et al, 2014;Wang et al, 2016). The interest in insect AMPs is based on the knowledge from ancient times, where different insects were used in the treatment of a number of different ailments (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…AMPs are considered growth and health promoters with modulating effects on the intestinal microbiome and do not result in the development of natural bacterial resistance (Wen and He, 2012;Choi, 2013a,b;Xiao, 2015;Józefiak and Engberg, 2017). Therefore, the aim of the present study was to examine the effect of the application of full-fat insect meals as a feed additive (0.05-0.2%) 'on top' of complete diets on the growth performance and GIT microbiota composition of broiler chickens.…”
Section: Introductionmentioning
confidence: 99%